TRAIT COMPENSATION AND SEX‐SPECIFIC AGING OF PERFORMANCE IN MALE AND FEMALE PROFESSIONAL BASKETBALL PLAYERS. (1st May 2014) - Lailvaux, Simon P.; Wilson, Robbie; Kasumovic, Michael M.
Abstract: Phenotypic traits are often influenced by dynamic resource allocation trade‐offs which, when occurring over the course of individual lifespan, may manifest as trait aging. Although aging is studied for a variety of traits that are closely tied to reproduction or reproductive effort, the aging of multiple traits related to fitness in other ways are less well understood. We took advantage of almost 30 years of data on human whole‐organism performance in the National Basketball Association (USA) to examine trends of aging in performance traits associated with scoring. Given that patterns of aging differ between sexes in other animal species, we also analyzed a smaller dataset on players in the Women's National Basketball Association to test for potential sex differences in the aging of comparable traits. We tested the hypothesis that age‐related changes in a specific aspect of overall performance can be compensated for by elevated expression of another, related aspect. Our analyses suggest that the aging of performance traits used in basketball is generally characterized by senescence in males, whereas age‐related changes in basketball performance are less evident in females. Our data also indicate a different rate of senescence of different performance traits associated with scoring over a male's lifetime.